Greening corporations via corporate law: implementation of article 22 CSDDD via a Climate Quota - Marc-Philippe Weller; Theresa Hößl; Camilla Seemann (npj Climate Action)
The European Union must be climate neutral by 2050. However, recent studies show that meeting this target will require many more measures than currently established to combat climate change. On behalf of article 22 Corporate Sustainability Due Diligence Directive of the European Union and given the biennial conference of the Association of German Jurists that took place in autumn 2024, the following article analyses how a “climate quota” for large businesses could be one further step in “Greening Corporate Law”.